(untitled) (Research, Society and Development, 2026)
Sports practices developed within social projects have been recognized as relevant spaces for educational and psychosocial formation, especially in working with children and adolescents in contexts of social vulnerability. Among these practices, skateboarding stands out due to its unique configuration, marked by bodily experimentation, peer interaction, and learning through trial and error, while also being understood as a cultural and identity practice within youth contexts. This article aims to present an experience report with an interpretative analysis, developed from the immersion in a social skateboarding project for children and adolescents. The research adopts a qualitative approach, utilizing participant observation and field diary records, analyzed through the lenses of Developmental Psychology, Sport Psychology, and non-formal education. The observed situations indicate that skateboarding acts as a mediator for social bonds, favors emotional processing in the face of frustration, and is associated with the building of feelings of belonging and recognition recurrent aspects in studies on sports and social development. Furthermore, the central role of educators is highlighted in maintaining a safe and formative environment where mistakes are integrated into the learning process. The analyzed experience allows for a reflection on the potential of skateboarding as an educational and psychosocial practice in social projects, emphasizing the importance of continuous monitoring and pedagogical intentionality.